An exploration into the meaning of death - Todres, Leslie Allen (Rhodes University, Faculty of Humanities, Department of Psychology, 1980)
From Preface: The present study attempts to explore, both theoretically and empirically, some implications that a personal consideration of death may have for the way we live our lives. Existential-Phenomenology has concerned itself with the description of the dimensions of human existence. It is in this enquiry that Death, and through it, human finitude, emerges as an important dimension of existence. It is not the fact of death itself, but the MEANING it has for our lives which may be of important consequence. It is to this area that this research addresses itself. The methodology employed arises out of a concern to contribute to the establishment of Psychology as a Human Science. To this end, a chapter focusing on the philosophical bases of methodology is included. It is hoped that this study may, however little, contribute both to the field of Thanatology as well as to the more theoretical issue of what Psychology is, and where it is going.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Death -- Psychological aspects